4x=-3y+17 becomes 4x+3y=17
4x+3y=17
3x-4y=-6
alrighty
elimination
muliply first equation by 4 and 2nd by 3 and add them
16x+12y=68
9x-12y=-18
add them
25x+0y=50
25x=50
idivide both sides by 25
x=2
sub back
3x-4y=-6
3(2)-4y=-6
6-4y=-6
-4y=-12
y=3
(x,y)
(2,3)
In Binomial distribution, the expected value or mean is given by,
E(X) = np
where, p = probability of success and n=number of sample size.
E(X) = 100×0.4 = 40
Answer: 3 inches, the triangles are the same
60 degrees, the triangles ae the same
Step-by-step explanation:
Answer:
<u>=-2y</u>
Step-by-step explanation:
y-3y
<u>=-2y</u>